A Case of Early-Stage Ovarian Carcinoid Tumor Metastasized to the Liver. (26th December 2012) - Kanayama, Seiji; Yamada, Yoshihiko; Tanase, Yasuhito; Haruta, Shoji; Nagai, Akira; Kawaguchi, Ryuji; Yoshida, Shozo; Furukawa, Naoto; Oi, Hidekazu; Kobayashi, Hiroshi
Abstract : We report a case of ovarian carcinoid tumor that recurred with multiple liver metastases and was successfully treated with chemoembolization. A 76-year-old woman was admitted to our hospital presented with abdominal distension and abnormal uterine bleeding for about 6 months. She presented with hyperestrogenic and androgenic manifestations such as vaginal bleeding with endometrial hyperplasia and hirsutism. Magnetic resonance (MR) imaging revealed a large solid and cystic ovarian tumor of 17 cm at maximum diameter. On the basis of the clinical diagnosis of sex cord stromal tumor containing a mature cystic teratoma, she underwent total abdominal hysterectomy and bilateral salpingo-oophorectomy. The pathology report revealed that the mass in the left ovary was a carcinoid tumor, insular type, with mature cystic teratoma. Two years after surgical treatment, multiple liver metastases were revealed by abdominal CT. Hepatic arterial infusion of cisplatin was performed for 2 courses, and multiple metastatic nodules have remarkably reduced. No established chemotherapy or radiation therapy treatments are currently available for recurrent or advanced carcinoid tumors. Our paper suggests that chemoembolization with cisplatin may be effective in treatment of patients with multiple liver metastases of ovarian carcinoid tumor.